TINJAUAN PENGARUH KELENGKAPAN DOKUMEN REKAM MEDIS PASIEN BPJS RAWAT INAP GUNA MENUNJANG KELANCARAN KLAIM INA-CBG’S DI RUMAH SAKIT BHAYANGKARA TK. II SARTIKA ASIH BANDUNG - Rohaeni, Neni; Maulida, Meyta (Jurnal TEDC, 2025)
Based on the preliminary strudy conducted in February 2024 at RS Bhayangkara TK.II Sartika Asih Bandung, out of 58 patient files of BPJS inpatient care in December 2023, there were 13 (22,4%) incomplete files. This study aims to determine the Influence of completeness of BPJS Inpatient Medical Record Documents to Support the Smoothness of INA-CBG’S Claims at Bhayangkara TK. II Sartika Asih Hospital in Bandung. The research method used in descriptive with a quantitative approach. The population in this study is the medical record summary forms of BPJS patients in the Fajar ward during the 2023 period at RS Bhayangkara TK.II Sartika Asih Bandung, totaling 100 forms. The samples taken from the population consist of all 100 samples. Data collection techniques employed include observation, interviews, and literature study. Research instruments include interview guidelines, sheets, checklists, writing instruments, and recording tools. Data processing techniques involve editing and tabulation. The research result indicate that the implementation of filling out BPJS Patient Medical Record Summaries at RS Bhayangkara TK. II Sartika Asih Bandung has not been carried out according to regulations by the relevant officers due to the absence of Operational Standard Procedure (SPO) governing the filling and flow of medical summaries. Consequently, BPJS patient medical record summaries are not 100% complete. Out of 100 samples of inpatient medicar records in the Fajar ward in 2023, only 83 (82,7%) summaries were complete. The author suggests creating SOP for filling out medical record summaries, conducting awareness campaigns for attending physicians to fill out diagnoses and procedures in BPJS Patient Medical Record Summaries.